Distinct Mitochondrial Remodeling During Mesoderm Differentiation in a Human-Based Stem Cell Model - Mostafavi, Sepideh; Balafkan, Novin; Pettersen, Ina Katrine Nitschke; Nido, Gonzalo S.; Siller, Richard; Tzoulis, Charalampos; Sullivan, Gareth J.; Bindoff, Laurence A. (Frontiers in Cell and Developmental Biology, 2021)
Given the considerable interest in using stem cells for modeling and treating disease, it is essential to understand what regulates self-renewal and differentiation. Remodeling of mitochondria and metabolism, with the shift from glycolysis to oxidative phosphorylation (OXPHOS), plays a fundamental role in maintaining pluripotency and stem cell fate. It has been suggested that the metabolic “switch” from glycolysis to OXPHOS is germ layer-specific as glycolysis remains active during early ectoderm commitment but is downregulated during the transition to mesoderm and endoderm lineages. How mitochondria adapt during these metabolic changes and whether mitochondria remodeling is tissue specific remain unclear. Here, we address the question of mitochondrial adaptation by examining the differentiation of human pluripotent stem cells to cardiac progenitors and further to differentiated mesodermal derivatives, including functional cardiomyocytes. In contrast to recent findings in neuronal differentiation, we found that mitochondrial content decreases continuously during mesoderm differentiation, despite increased mitochondrial activity and higher levels of ATP-linked respiration. Thus, our work highlights similarities in mitochondrial remodeling during the transition from pluripotent to multipotent state in ectodermal and mesodermal lineages, while at the same time demonstrating cell-lineage-specific adaptations upon further differentiation. Our results improve the understanding of how mitochondrial remodeling and the metabolism interact during mesoderm differentiation and show that it is erroneous to assume that increased OXPHOS activity during differentiation requires a simultaneous expansion of mitochondrial content.